Nutrition for sport, exercise, and health - Spano, Marie A. MS, RD, CSCS, CSSD; Kruskall, Laura J. PhD, RDN, CSSD, LD, FACSM, FAND; Thomas, D. Travis PhD, RDN, CSSD, LD, FAND
Nutrition for sport, exercise , and health, second edition, blends applied content with updated research-based guidelines to help students distinguish between nutrition recommendations backed by science and the plethora of misinformation available in the field. Students first discover the role nutrition plays in overall well-being. Next, they learn the role that support health and active lifestyle. Then, the function of micronutrients in health and performance is covered. Finally, the text concludes with the application of nutrition principles, with guideance on how to properly fuel for sport, exercise, and health